2017
DOI: 10.18034/apjee.v4i1.237
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and Bioethanol Production from Oil Palm Trunk (OPT)

Abstract: Various types of carbohydrate-rich plants with several methods have been experimented to produce sugar and bioethanol. Usually, sugar and bioethanol are yielded by fermentation process synthesized from cellulosic and hemi-cellulosic biomass. In this study, Oil Palm Trunk (OPT) sap was utilized to produce sugar and bioethanol using Saccharomyces cerevisiae (Yeast) as fermentation agent as well as Alanine amino acid (C3H7NO2) and Epsom salt (MgSO4) as nutritional supplements in anaerobic condition with 96 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
2
5
0
1
Order By: Relevance
“…It was concluded that the saccharification had decreased with certain timeperiod and the experiment was not continued further after day 7. This study was a continuation of that of Hossain and Jalil (2015). According to Hossain and Jalil (2015), from day 1 to day 4, the saccharification rate for OPT increased continuously while this study has extended this finding identifying the further saccharification until day 10 (shown in Table 2) and day 7 (shown in Table 3).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…It was concluded that the saccharification had decreased with certain timeperiod and the experiment was not continued further after day 7. This study was a continuation of that of Hossain and Jalil (2015). According to Hossain and Jalil (2015), from day 1 to day 4, the saccharification rate for OPT increased continuously while this study has extended this finding identifying the further saccharification until day 10 (shown in Table 2) and day 7 (shown in Table 3).…”
Section: Resultssupporting
confidence: 52%
“…This study was a continuation of that of Hossain and Jalil (2015). According to Hossain and Jalil (2015), from day 1 to day 4, the saccharification rate for OPT increased continuously while this study has extended this finding identifying the further saccharification until day 10 (shown in Table 2) and day 7 (shown in Table 3). The previous study outlined the increased OPT saccharification rate from day 1 to 4 for both samples, with and without supplements.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Most of the kitchen waste was similar feedstock to lignocellulosic raw materials, which is considered to be an excellent substrate 22 . Previous works delineated the pathway of converting plant-based waste biomass to bioethanol, in which enzyme pretreatment was conducted before yeast fermentation [23][24][25][26] . Gnansounou & Dauriat produced 30.9 g bioethanol and 65.2 L biogas using 1 kg of kitchen waste 27 .…”
Section: Discussionmentioning
confidence: 99%